Dieta de lagartos e serpentes atropelados em rodovias do semiárido nordestino no estado do Rio Grande do Norte, RN - Cabral, Sofia de Oliveira (2019)
Studies about natural history of lizards and snakes are yet scarce for the Caatinga biome or descriptions are disaggregated and isolated in different physionomys of Caatinga. Species of lizards and snakes occupy different positions at the trophic level and has a great importance in the diagnosis of biotic and abiotic effects on the environment. The present study was carried out by necropsy from road-killsanimals of roads surrounding three Federal Conservation Units: Furna Feia National Park, Açu National Forest and Seridó Ecological Station. The road-kill animals were carry to the Ecology and Wildlife Conservation Laboratory at the Federal Rural Semi-Arid University to identify the species, morphometry and diet analysis. The general objective of the project was to characterize the food habits of different species of lizards and snakes road-kills. The study of the diets allows greater amplitude on the information not only ecological but also about behavior and physiological. This range of knowledge also contributes to the conservation of the species studied